Kesederhanaan Pribadi Nabi Muhammad dan Aplikasinya Dalam Fakta Sosial: (Sebuah Kajian Nilai Al-Qurâ€™an dan Hadis) - Khairil Ikhsan Siregar (Islamic Religious Education Departement, 2013)
The peper speeching about: â€œSimplicity Personal of Prophet Muhammad and Its Application in Social Factsâ€. Psychological of Prophet already ingrained from childhood to adulthood, with the emergence of consciousness, initiative, creative, empathetic, as joining to help his uncle Abdul Muttalib lighten the work of his uncle, so his grandfather and his uncle unfortunately, to himself as a substitute for parents. Will allow the Prophet for scuba. This personality produced social intraction both to individuals or to the public, such as the Prophet has reconciled the dispute among the tribes when want to return the stone of the black stone to the place of beginning, and others. But that personality, although after appointed a prophets and apostles and became leader the ummat in one islamic state, turns social intercourse prophet still an humble, earthy, and egaliter. It, many in deed prophet memasyarakat, sit with his people bitter tasting and delighted together. Prophet not use his authority to enrich up–and but he was more prioritizing everybody else than himself and his family.